Identifying factors contributing to kinesiophobia in patients post-percutaneous coronary intervention - Lu Chen; Jiang-Ying Li; Zhen-Qing Ren; Li-Chun Wang; Pei-Yu Huang; Wen-Juan Jiang; Cong Li; Li Ding (BMC Nursing)
Abstract Objective This study aims to investigate the factors contributing to kinesiophobia in patients following percutaneous coronary intervention (PCI). Methods Purposive sampling was employed to conduct semi-structured interviews with 14 patients and 4 healthcare professionals who satisfied the inclusion and exclusion criteria, from May 2023 to June 2023. Data were coded, categorized, and thematically analyzed using the Colaizzi seven-step analysis method. Results The factors contributing to kinesiophobia in patients post-PCI were classified into four primary themes: heightened psychological stress, increased uncertainty regarding exercise, reduced self-efficacy, and inadequate support systems. Conclusion Kinesiophobia in patients post-PCI hinders adherence to cardiac rehabilitation protocols. Early identification and analysis of the factors contributing to kinesiophobia can guide the development and implementation of effective intervention strategies. Clinical registration number Not applicable.